Optimalisasi Pembelajaran Koperasi dengan Kekuatan Digital Storytelling - Ariyanti Ariyanti (Jurnal Pendidikan Ekonomi, 2021)
Economic learning cooperative material in class X SMA often leads to confusion and foreign effects on students, because there is no "real" cooperative around them. The concept of a populist economy that is carried by cooperative is like untouched, idealism that is not easily understood, students do not understand what the noble ideals of cooperative are to be present in society. This is exacerbated by the conditions of learning in the pandemic era. Despite the difficulties, it is undeniable that digital technology-based learning makes students stronger to bear the name Z generation who are accustomed to the internet and technological sophistication. Digital Storytelling (DS) comes with the concept of digital story, easy access, and it is hoped that it will be easier to digest by students who are familiar with cyberspace and digitization in various fields. The research uses the literature study method by examining research results, written data and documents related to project-based learning, cooperative and digital storytelling. Based on these studies, it is known that the use of DS in cooperative learning  materials is very possible because DS is able to illustrate abstract concepts to be more real, build 21st century skills, increase learning effectiveness and efficiency, train communication and collaboration and increase student learning motivation. DOI: https://dx.doi.org/10.17977/UM014v14i22021p97